1998
DOI: 10.4141/a97-089
|View full text |Cite
|
Sign up to set email alerts
|

Intake, digestibility, methane and heat production in bison, wapiti and white-tailed deer

Abstract: . 1998. Intake, digestibility, methane and heat production in bison, wapiti and white-tailed deer. Can. J. Anim. Sci. 78: 681-691. A 3 × 2 factorial experiment was conducted in which the digestibility of alfalfa pellets and methane and heat productions were measured in bison, wapiti and white-tailed deer in February/March 1995 and in April/May 1995. Voluntary dry matter intake (DMI) while animals were individually fed averaged 70, 87 and 68 g kg -0.75 d -1 , respectively (P = 0.05), and was generally higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 33 publications
(35 reference statements)
3
22
1
1
Order By: Relevance
“…1, 2c). The quadratic model is also congruent with decades of research on digestive physiology, demonstrating that elk are less adapted to processing grass than obligate grazers, but more adapted than obligate browsers (Mould and Robbins 1982;Wickstrom et al 1984;Baker and Hansen 1985;Galbraith et al 1998). Conversely, elk are less adapted to processing browse than obligate browsers, but more adapted that obligate grazers (Ward 1971;Mould and Robbins 1982;Baker and Hobbs 1987;Bellows et al 1996;Dehority et al 1999).…”
Section: Discussionsupporting
confidence: 68%
“…1, 2c). The quadratic model is also congruent with decades of research on digestive physiology, demonstrating that elk are less adapted to processing grass than obligate grazers, but more adapted than obligate browsers (Mould and Robbins 1982;Wickstrom et al 1984;Baker and Hansen 1985;Galbraith et al 1998). Conversely, elk are less adapted to processing browse than obligate browsers, but more adapted that obligate grazers (Ward 1971;Mould and Robbins 1982;Baker and Hobbs 1987;Bellows et al 1996;Dehority et al 1999).…”
Section: Discussionsupporting
confidence: 68%
“…This resulted in a longer rumen retention time and increased CH 4 production. Galbraith et al (1998) reported CH 4 losses of 6.6, 5.2 and 3.3% GEI for bison (Bison bison), wapiti (Cervus elaphus) and white-tail deer (Odocoilleus virgianus), respectively, when fed lucerne pellets, with the lowered trend of CH 4 production corresponding with a reduction in retention time with the smaller animals.…”
Section: Resultsmentioning
confidence: 99%
“…These include the use of respiration calorimetry chambers (Kelly et al 1994;Galbraith et al 1998;Murray et al 1999), isotopic techniques (Murray et al 1976;France et al 1993), tracer techniques [sulfur hexafluoride (SF 6 )], Kaharabata et al 2000; and mass balance/micrometeorological techniques (Lassey et al 1997;Sauer et al 1998;Harper et al 1999). The advantages and disadvantages of each method have been reviewed by Johnson and Johnson (1995).…”
Section: Measurement Of Methane Emission From Dairy Cattlementioning
confidence: 99%